TINJAUAN PENERAPAN NINE LIFE SAVING PATIENT SAFETY SOLUTIONS (STUDI KASUS DI RS PKU MUHAMMADIYAH BANTUL) - Kusuma Arbianti; Aris Suparman; Qurrotul Aini (ODONTO : Dental Journal, 2015)
Background: Patient safety already a high priority in the health service aspect in the hospital and has become demands of the needs in the health services, as it will hopefully minimize the risk of unexpected occurrences. Reducing the conflict between health workers and patients, reducing the incidence of medical disputes, reducing the demands and legal proceedings and administrative charges of malpractice accusation are getting more and more against hospital. WHO Collaborating Centre for Patient Safety has published Nine Life Saving Patient Safety Solutions. The purpose of this research was to review and analyze the application of nine life saving patient safety solutions in RS PKU Muhammadiyah Bantul.Method: This case study was qualitative to review nine life saving safety patient solutions in RS PKU Muhammadiyah Bantul. The data has been collected with interview, observation, and analysis of documents in RS PKU Muhammadiyah Bantul. The research was held in RS PKU Muhammadiyah Bantul in October 2011. The object of this research is RS PKU Muhammadiyah Bantul. While the subject of this research is the chairman of the patient safety team, Assistant Manager of Pharmacy, Assistant Manager of ICU, Assistant Manager of surgery room, Assistant Manager of Emergency room, Assistant Manager of nursing, head of the ward hall Al Kahfi, head of the ward hall Al A€™raf, and the head of the ward hall Ar Rahman. Result: This study shows that the patient safety program in PKU Muhammadiyah Bantul was still initiated and built, whereas the implementation of nine life saving patient safety solutions program is not yet specific and detailed. However there are a few items from these items are already implemented and can become input in the implementation of the nine life saving patient safety solutions program.Summary: The implementation of nine life saving patient safety solutions program is not yet specific. However there are a few items from these items are already implemented and can become input in the implementation of the nine life saving patient safety solutions program.